Features of control measures when learning historical grammar with a credit-modular approach (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article presents the author's approach to monitoring the quality of students' knowledge of historical grammar of the Ukrainian language taught by thematic modules. Examples of tests for historical morphology are suggested.
Keywords: historical grammar; thematic module; control level